Low Circulating Levels of Omentin-1 and Irisin in Type 2 Diabetes Mellitus Patients with Metabolic-Associated Fatty Liver Disease - Li, Hua-Ying; Zhang, Yan-Yan; Cai, Xia-Ming; Chen, Xiang (Turkish Journal of Gastroenterology, 2025)
Background/Aims: The study analyzed the roles of circulating omentin-1 and irisin in patients with type 2 diabetes mellitus (T2DM) concomitant with metabolic-associated fatty liver disease (MAFLD). Materials and Methods: This cross-sectional study included 80 patients with T2DM but no MAFLD, 62 patients with MAFLD but no T2DM, 50 T2DM patients having MAFLD (T2DM/MAFLD), and 80 healthy individuals. Results: The serum levels of omentin-1 and irisin were both significantly reduced in patients with T2DM coexisting with MAFLD com pared to T2DM or MAFLD patients alone. In T2DM patients, the level of omentin-1 decreased as the level of fasting plasma glucose (FPG) increased and the level of high-density lipoprotein cholesterol (HDL-C) reduced; the level of irisin decreased as the levels of FPG and fasting insulin (FINS) increased. In MAFLD patients, a lower level of omentin-1 was correlated with a lower level of HDL-C but with a greater waist-to-hip ratio (WHR), alanine aminotransferase and aspartate aminotransferase levels; a lower level of irisin was correlated with higher WHR and FINS level. In patients with T2DM coexisting with MAFLD, those with a lower level of omentin-1 were found to have a lower level of HDL-C concurrent with lower WHR and triglyceride level; and those with a lower level of irisin showed lower WHR, FPG and FINS levels. Combined evaluation of omentin-1 and irisin for diagnosing T2DM coexisting with MAFLD yielded an area under the curve of 0.943. Conclusion: These findings suggest the assessment potential of omentin-1 and irisin for T2DM coexisting with MAFLD. Cite this article as: Li H-Y, Zhang Y-Y, Cai X-M, Chen X. Low circulating levels of omentin-1 and irisin in type 2 diabetes mellitus patients with metabolic-associated fatty liver disease. Turk J Gastroenterol. 2025;36(7):450-458.